Exploiting hydrophobic borohydride-rich ionic liquids as faster-igniting rocket fuels. Issue 10 (21st December 2015) - Liu, Tianlin; Qi, Xiujuan; Huang, Shi; Jiang, Linhai; Li, Jianling; Tang, Chenglong; Zhang, Qinghua
Abstract : A new family of hypergolic ionic liquids with ultra-short ignition delay times was designed and synthesized as potential rocket fuels. Abstract : A family of hydrophobic borohydride-rich ionic liquids was developed, which exhibited the shortest ignition delay times of 1.7 milliseconds and the lowest viscosity (10 mPa s) of hypergolic ionic fluids, demonstrating their great potential as faster-igniting rocket fuels to replace toxic hydrazine derivatives in liquid bipropellant formulations.